2016
DOI: 10.5535/arm.2016.40.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Nitric Oxide Synthase 1 Affects the Clinical Phenotypes of Ischemic Stroke in Korean Population

Abstract: ObjectiveTo investigate whether four single nucleotide polymorphisms (SNPs) rs2293054 [Ile734Ile], rs1047735 [His902His], rs2293044 [Val1353Val], rs2682826 (3'UTR) of nitric oxide synthase 1 (NOS1) are associated with the development and clinical phenotypes of ischemic stroke.MethodsWe enrolled 120 ischemic stroke patients and 314 control subjects. Ischemic stroke patients were divided into subgroups according to the scores of the National Institutes of Health Stroke Survey (NIHSS, <6 and ≥6) and Modified Bart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…NO is the main inhibitor of the esophageal myenteric plexus, meaning that it progressively delays muscle contraction in the esophagus, and in this context, carriers of the variant genotype of this polymorphism may have a lower function of the gene. In addition, other studies contribute to this argument, in which the variant allele of rs2682826 is associated with a lower function of the gene [ 29 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…NO is the main inhibitor of the esophageal myenteric plexus, meaning that it progressively delays muscle contraction in the esophagus, and in this context, carriers of the variant genotype of this polymorphism may have a lower function of the gene. In addition, other studies contribute to this argument, in which the variant allele of rs2682826 is associated with a lower function of the gene [ 29 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Associations of NOS1 with various diseases have been reported, such as schizophrenia, Parkinson’s disease, suicide, achalasia, multiple sclerosis, ischemic stroke, and hypertension. In previous studies found that the T allele of rs2293054 was associated with lower NIHSS scores and with NIHSS scores of ischemic stroke patients in different inherited model [ 43 ]. But in our result, rs2293054 showed no relationship with CP.…”
Section: Discussionmentioning
confidence: 99%
“…The synonymous SNP (rs2682826) located in the 3’-UTR of exon 29 of the NOS1 gene was selected as the tag SNP for one of the most frequent haplotypes. The SNP rs2682826 is located close to several miRNA-binding sites in the gene’s 3′-UTR, and it likely affects the stability and translational efficiency of mRNA [ 43 45 ]. Some polymorphisms in NOS1 gene can directly affect the expression of mRNA, which change the levels of NO [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 Also, NO modulates immuneregulation, surfactant maturation or secretion. 11 In this study, we found statistical increases in TT, GT+TT genotype and T allele among RDS compared to controls.…”
Section: Resultsmentioning
confidence: 99%
“…1 Congenital anomalies, inherited metabolic disorders and sepsis were excluded. Neonates were subjected to history taking, general and local examinations; APGAR score [normal (8)(9)(10), mild (6)(7)(8), moderate (3)(4)(5), severe (0-2)]. Complete blood count and arterial blood gas were performed (ABG for RDS neonates only).…”
Section: Methodsmentioning
confidence: 99%